SKIP and BIR-1/Survivin have potential to integrate proteome status with gene expression - Kostrouch, David; Kostrouchová, Markéta; Yilma, Petr; Chughtai, Ahmed Ali; Novotný, Jan Philipp; Novák, Petr; Kostrouchová, Veronika; Kostrouchová, Marta; Kostrouch, Zdeněk (Journal of proteomics, 2014)
UNLABELLED: SKIP and BIR are evolutionarily conserved proteins; SKIP (SKP-1) is a known transcription and splicing cofactor while BIR-1/Survivin regulates cell division, gene expression and development. Their loss of function induces overlapping developmental phenotypes. We searched for SKP-1 and BIR-1 interaction on protein level using yeast two-hybrid screens and identified partially overlapping categories of proteins as SKIP-1 and BIR-1 interactors. The interacting proteins included ribosomal proteins, transcription factors, translation factors and cytoskeletal and motor proteins suggesting involvement in multiple protein complexes. To visualize the effect of BIR-1 on the proteome in Caenorhabditis elegans we induced a short time pulse BIR-1 overexpression in synchronized L1 larvae. This led to a dramatic alteration of the whole proteome pattern indicating that BIR-1 alone has the capacity to alter the chromatographic profile of many target proteins including proteins found to be interactors in yeast two hybrid screens. The results were validated for ribosomal proteins RPS3 and RPL5, non-muscle myosin and TAC-1, a transcription cofactor and a centrosome associated protein. Together, these results suggest that SKP-1 and BIR-1 are multifunctional proteins that form multiple protein complexes in both shared and distinct pathways and have the potential to connect proteome signals with the regulation of gene expression. BIOLOGICAL SIGNIFICANCE: The genomic organization of the genes encoding BIR-1 and SKIP (SKP-1) in C. elegans have suggested that these two factors, each evolutionarily conserved, have related functions. However, these functional connections have remained elusive and underappreciated in light of limited information from C. elegans and other biological systems. Our results provide further evidence for a functional link between these two factors and suggest they may transmit proteome signals towards the regulation of gene expression.
Keywords: Signal Transduction; Survivors; zvířata; přežívající; Proteome; proteiny Caenorhabditis elegans; Animals; regulace genové exprese; jaderné proteiny; Caenorhabditis elegans; Gene Expression Regulation; signální transdukce; Nuclear Proteins; proteom; Caenorhabditis elegans Proteins